Pembentukan emergence profile yang optimal mempengaruhi pemasangan prothesis - Carolina, Inge; Suwandi, Trijani (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: The emergence profile in dental implants can be defined as the contour of an implant restoration as it emerges from the implant platform. Case report: A 67-year-old woman has implant placement on teeth 14 and 35 using two different implant systems (implant direct and strauman), where the design platforms of these 2 types of implant systems influence the formation of the emergence profile. Conclusion: Emergence profile design is important for stable peri-implant tissue and esthetically pleasing result with implant restoration